Capturing brand loyalty through customer relationship management: exploring the roles of customer brand engagement and psychological contracts from a dual perspective - Lingzhi Brian Fang; Tan Cheng; Heng Yang; Yajing Duan (Humanities & Social Sciences Communications)
Abstract Customer brand engagement has always been emphasized by numerous firms on digital media. However, previous studies of customer brand engagement did not reveal its features and functions, which impedes our ability to further comprehend and apply it. Based on psychological contract theory, this study identified a mechanism of customer brand engagement and loyalty for exploring customer brand engagement features and functions. We collected 575 valid questionnaires and then used structural equation modeling (SEM) and response surface method (RSM) to verify the theoretical model. The findings of this study show that the psychological and behavioral aspects of customer brand engagement have distinctive effects on brand loyalty. As a mediator, a psychological contract plays an aligned role and provides socioemotional and economic perspectives for explaining this mechanism. When RSM is used, the congruence effect of these 2 features has been revealed, and thereby, various functions of customer brand engagement interior parts have been verified. This novel viewpoint improves our theoretical comprehension of customer brand engagement. Additionally, it also facilitates our practical understanding of customer relationship management strategies and brand loyalty system construction through customer brand engagement from a practical perspective.